Website benchmarking: an abridged WAM study. Issue 7 (3rd October 2016) - Cassidy, Leonie Jane; Hamilton, John
Abstract : Purpose: Website benchmarking theory and the website analysis method (WAM) are benchmark tested across non-commercial tropical tourism websites. The paper aims to discuss this issue. Design/methodology/approach: The abridged WAM benchmarks 280 tropical tourism websites from four continental areas (Africa, Asia, Oceania, and The Americas) and presence or absence of website components objectively rank-scores. Across locations significant website benchmark score differences are determined. In all, 20 of these websites are ranked by an eight expert focus group. These experts also seek-out the existence of allocated common website components. Findings: The abridged WAM approach is suitable for benchmarking tropical tourism websites. Website benchmarking scores at-level are determined. At the website, domain, and function levels significant continental area differences exist. Experts cross-check the study. They find it easier to rank websites with fewer components, and show split decisions when determining the existence of common website components. Research limitations/implications: This study's abridged version of WAM uses publicly viewable components to show significant differences across website scores, and identifies some missing components for possible future inclusion on the website, and it also supports the WAM benchmarking theory approach. Practical implications: Website managers/owners can apply WAM (or an abridged WAM) to benchmark their websites. WAM is theoretically supported and it systematically allows comparison against the universal set of components and/or against competitor websites. A full or abridged WAM approach to website benchmarking is preferable to subjective or survey-based approaches. Originality/value: This study successfully applies the Cassidy and Hamilton (2016) theory and approach to practical website benchmarking.